ANALISIS DAMPAK BERBAGI SUMBER DAYA PADA KESEJAHTERAAN INDIVIDU: BUKTI EMPIRIS BAHWA BERBAGI TIDAK MENYEBABKAN KEMISKINAN - Danang Nugroho; Rio Sutrisno; Wildan Nurdiansyah Fadila; Vian Restu Ramanda; Nazar Indra Pratama; Muhamad Fauzan Ferdiansyah; Putri Aulia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Berbagi Nasi movement aims to foster hope and a spirit of sharing by providing simple meals, countering prevailing individualistic attitudes. This qualitative research explores the impact of the Sharing Principle on preventing impoverishment, delving into the roles of Berbagi Nasi advocates and assessing individual and collective impacts. Conducted at Iteung - Abah Tatang's shop in Bandung, the study utilizes participant observation and documentation to gather data on the advocates' activities. Findings reveal two crucial roles played by Berbagi Nasi Bandung advocates: serving as role models and developing rice-sharing activities, particularly involving young family members to instill care from an early age. Drawing from Daniel Batson's theory, the research emphasizes that sharing involves deeper motivations beyond poverty avoidance, focusing on motivation rather than consequences. Recommendations include developing educational programs to alter public perceptions, encouraging community sharing, emphasizing character development through sharing activities, implementing sustainable monitoring and evaluation systems, and promoting inclusive sharing initiatives. These initiatives aim to dispel the notion that sharing leads to poverty, fostering a societal shift toward altruism and contributing to the overall well-being of individuals and communities. The keywords encompass the Sharing Principle, Berbagi Nasi advocates, poverty prevention, community sharing, character development, sustainable monitoring, inclusive sharing initiatives, societal shift toward altruism, and societal well-being.